International perspectives on value creation and sustainability through social entrepreneurship - Magd, Hesham; Singh, Dharmendra; Taqui, Syed Raihan; Spicer, David (IGI Global, 2022)
This book explores various issues and ideas about social entrepreneurship through the lens of theoretical, practical, and empirical research, providing an international outlook of social entrepreneurship, focusing primarily on value creation and sustainability.
Includes bibliographical references and index. - Mode of access: World Wide Web
Keywords: Social entrepreneurship; Value; Sustainable development; Nachhaltigkeit